Volleyball injuries of the lower extremity - Frey, C.; Feder, K.
Injuries to players on the U.S. Volleyball Association (USVBA) National Team and participants in the Association of Volleyball Professionals (AVP) Beach Tour have been recorded for several years [Figure 1]. Foot and ankle injuries to the USVBA indoor players comprised 19.8 percent of the total, with ankle injuries (10.8 percent) slightly greater than foot injuries (9 percent). Ankle injuries ranked third, behind shoulder and knee injuries. On the beach, foot and ankle injuries ranked fourth, behind injuries to the lumbar region, shoulder, and knee. Lower extremity volleyball injuries can be divided into two types: overuse and traumatic. Common overuse injuries occur at the anterior tibial and posterior tibia muscles and the Achilles tendon. Plantar fasciitis, metatarsal stress fractures, and navicular stress fractures also occur at a fairly high rate. Traumatic injuries include ankle sprains, avulsion fractures to the fifth metatarsal base, Jones fractures, Achilles tendon ruptures, hyperextension of the first metatarsophalangeal (MTP) joint with secondary hallux rigidus, and hyperflexion of the MTP joints with secondary instability and capsulitis.